Bowland Shale well placement strategy – Part 1: Determining landing intervals using geomechanical properties. (November 2021) - Anderson, Iain; Ma, Jingsheng; Wu, Xiaoyang; Stow, Dorrik; Griffiths, David
Abstract: The production performance of a shale reservoir is directly affected by the geomechanical characteristics of the formation. A target shale interval will ideally develop hydraulic fractures upon stimulation that stay open with the aid of injected proppant. However, shales are geomechanically complex due to heterogeneities in their rock properties such as mineralogy and porosity and the extent to which they may be naturally fractured. These characteristics can complicate the task of identifying the ideal target interval for placing horizontal wells. Whilst the Bowland Shale is the UK's most prospective shale gas target, long horizontal wells are generally not feasible or practical in the Craven Basin, due to the existence of many, large-offset reverse faults and high bedding dips. An alternative to this approach could include drilling shorter, stacked horizontal wells targeting different stratigraphic intervals. However, it is unclear if there are enough intervals within the stratigraphic section with the desired geomechanical properties to target with stacked horizontal wells, nor if there are adequate intervals that can limit vertical hydraulic fracture growth between those wells. The absence of the latter may ultimately lead to well interference and reduced production. These issues were addressed by the creation of a series of wireline log-based geomechanical logs at well Preese Hall-1, calibrated to pressure test data. Aided by the results of a cluster analysis model, the upper section of the Bowland Shale was classified into geomechanical zones to identify the optimal intervals for hydraulic fracturing and barriers to vertical hydraulic fracture growth. Three intervals are highlighted with low effective stress, low fracture toughness and high brittleness which may form excellent landing zones. Importantly, these landing zones are also separated by intervals of high effective stress that may limit vertical hydraulic fracture growth and mitigate the risk of well interference. Highlights: Geomechanical models reveal best landing points in the Bowland Shale stratigraphy. In some intervals, the Bowland Shale is overpressured, brittle and exhibits low effective stress. Cluster analysis aids in picking optimal combination of reservoir and mechanical properties. Highly stressed intervals between landing points may limit vertical fracture propagation and facilitate stacked drilling.